(untitled) (Bangladesh Journal of Botany, 2023)
A pot experiment was conducted to study the effect of vermicompost (VC), potassium (K) and boron (B) on the growth, yield and mineral nutrient accumulation of eggplant (Solanum melongena L.). Eight treatments were arranged in a completely randomized design (CRD) with three replications including control. Application of VC8K60 (T5) resulted in the highest plant height (60 cm). However, VC8K60B0.4 (T8) recorded the maximum leaf number (17 plant-1), leaf area (264 cm2), fruit petiole (4.15 plant-1), fruit number (3.50 plant-1), total fresh (143.15 g plant-1) and dry weight (16.4 g plant-1). Application of VC8K60B0.4 (T8) helped the improvement of the N, P, K, S, Fe and Zn concentrations of the roots, leaves and fruits. Result of growth, yield attributes and nutrient content varied significantly (p ≤ 0.05). Hence, to achieve higher fruit yield with higher nutrient concentration the soil should be supplied with vermicompost, muriate of potash (50% K) and boric acid (17% B) at a required rate. However, for a good recommendation field trials are needed in major agroecosystems of the country. Bangladesh J. Bot. 52(4): 959-964, 2023 (December)